Istikhdam Kitab "Al-Jurumiyyah" wa "Al-Amtsilah al-Tasrifiyyah" fi Ta'lim Qawaid al-Lughah al-'Arabiyyah bi Ma'had "Dar al-Hikmah" Al-Salafi Basuruwan - Ayun, Qurroti (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2017)
Abstrac :Islamic dormitory becomes Islamic Education Institution for Islamic studies and Arabic in Indonesia. It has Existed already since long time ago, one of them is Darul Hikmah Pandaan Pasuruan. Qowa’idul Lughoh (Grammar) is taught at the Islamic doormitory. This research aims to, 1st , describe the effectiveness of using al-jurumiyah and al amtsilatu al-tashrifiyah book in teaching Qowa’idul Lughoh from students interest field. 2nd describe the effectiviness of using al-jurumiyah and al amtsilatu al-tashrifiyah book in teaching Qowa’idul Lughoh from learning result.The method used in this research is quantitative descriptive. The data drives from teaching and learning proses. The data source in this research is 7 teachers and 41 students. The research instrument are interview, observation, quistionare and students score. This research was conducted from August to December 2016.The research finding shows that, 1st male students interest 84,69% and female students 81,60% toward the learning qowa’idul lughoh using al-jurumiyah and al amtsilatu al-tashrifiyah book. 2nd the average result of male students who use al-jurumiyah book improve from 72,78% to 83,33% and female students from 72,75% to 85,75%. Male students who use al-amtsilatu al-tashrifiyah book improve from 73,60% to 84,72%, female students from 74,50% to 86,25%. The conclusion is the using of -jurumiyah and al amtsilatu al-tashrifiyah book is effective in encourage the students interest and satisfied learning result.الكلمات الأساسية        : فعالية، تعليم ، قواعد اللغة العربية